2006
DOI: 10.1021/bi061556n
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Autophosphorylating Kinase Activities of Arabidopsis and Human Cryptochromes

Abstract: Cryptochromes are FAD-based blue-light photoreceptors that regulate growth and development in plants and the circadian clock in animals. Arabidopsis thaliana and humans possess two cryptochromes. Recently, it was found that Arabidopsis cryptochrome 1 (AtCry1) binds ATP and exhibits autokinase activity that is simulated by blue light. Similarly, it was reported that human cryptochrome 1 (HsCry1) exhibited autophosphorylation activity under blue light. To test the generality of light stimulated kinase function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 26 publications
6
65
0
Order By: Relevance
“…DNA binding. In contrast to the crystal structure of AtCRY1 (Brautigam et al 2004), a computational model of human CRY2 revealed that the DNA-binding groove of photolyase is conserved in human CRYs (Özgür and Sancar 2003). Not surprisingly, human CRY2 bound weakly to double-stranded DNA and with higher affinity to single-stranded DNA nonspecifically (Fig.…”
Section: Biochemical Propertiesmentioning
confidence: 86%
See 4 more Smart Citations
“…DNA binding. In contrast to the crystal structure of AtCRY1 (Brautigam et al 2004), a computational model of human CRY2 revealed that the DNA-binding groove of photolyase is conserved in human CRYs (Özgür and Sancar 2003). Not surprisingly, human CRY2 bound weakly to double-stranded DNA and with higher affinity to single-stranded DNA nonspecifically (Fig.…”
Section: Biochemical Propertiesmentioning
confidence: 86%
“…7A), with a K D~5 x 10 -9 , and with slightly higher affinity to a single-stranded DNA oligomer containing a (6-4) photoproduct, but there was no photorepair of the lesion. Human CRY1 exhibited similar DNA-binding properties (Özgür and Sancar 2003). Currently, the significance of these findings is not known.…”
Section: Biochemical Propertiesmentioning
confidence: 93%
See 3 more Smart Citations